Exploring perceptions and experiences of community people toward chhaupadi culture in Nepal: Social-ecological approach - Prayag Raj Joshi; Ram Krishna Maharjan (Journal of the Scientific Society, 2020)
The Chhaupadi culture contributes to the huge proportion of mother and infant mortality in Nepal. Despite a large provision in eliminating this culture in the last almost decades, the culture remains constant. The Chhaupadi Pratha after childbirth is still in practice, especially in Far-western province. Several quantitative studies described the Chhaupadi culture and some qualitative studies have also carried out on exploring the perceptions of community people regarding Chhaupadi culture, but most of the studies had taken this practice as only for monthly menstruation. To fill this gap, I aimed at exploring the perceptions of community people and their experiences related to Chhaupadi Pratha in Kailali district. A prospective qualitative study was conducted among thirty mothers and five other key informants from Godawari municipality. Data were collected through in-depth interviews, key informant interviews, and focus group discussions. Data analysis was guided by the Kenneth McLeroy's social-ecological model (SEM) including five levels of factors which influenced the maternal and child health (MCH) care practices of mothers. While mothers showed little decision-making autonomy, interpersonal factors played an important role in their use of modern health services. Besides, community and social factors as well as organizational and health system factors also shaped mothers' MCH care practices. To improve the MCH care practices of mothers, all the five levels of SEM should be taken into account while developing health programs targeting mothers.